Sistem Informasi Akademik Dengan Framework Codeigniter (Studi kasus : SMP N 1 Teras) - Rohmat, Alfi Nur; , Heru Supriyono, ST. MSc. PhD (2016)
SMPN 1 Terrace is one of the public schools located in the county which Boyolali academic information still use manual, the information submitted slower and less effective that require an academic information system in order to make a useful contribution to all parties, especially in supporting the advancement of the academic field. With the academic information system will facilitate the school in providing information about the assessments and other data is easily accessible, so that students can get the assessment information via the Internet. The purpose of this research is the manufacture of academic information systems is done using CodeIgniter framework and uses MySQL as database management that is popular used to build web applications using a data source and database management. The results of this study are academic information system that contains a variety of information, ie information assessment, teacher data, student data, school schedules, attendance, and print the value. Results of testing black box indicates the system runs well. Based on testing potential users state that agrees to the system are made.